Respuesta :

Simplify the following:

((-1^3)/(-3)^(-3))^2

1^3 = 1:
((-1)/(-3)^(-3))^2

(-3)^(-3) = 1/(-1)^3×1/3^3 = (-1)/3^3:
((-1)/((-1)/3^3))^2

3^3 = 3×3^2:
((-1)/(-1/(3×3^2)))^2

3^2 = 9:
((-1)/((-1)/(3×9)))^2

3×9 = 27:
((-1)/((-1)/27))^2

Multiply the numerator of (-1)/((-1)/27) by the reciprocal of the denominator. (-1)/((-1)/27) = (-27)/(-1):
((-27)/(-1))^2

(-27)/(-1) = (-1)/(-1)×27 = 27:
27^2

 | 2 | 7
× | 2 | 7
1 | 8 | 9
5 | 4 | 0
7 | 2 | 9:
Answer:  729 = 1/729 thus c: is your Answer
ACCESS MORE